2014
DOI: 10.1021/je500093z
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Physicochemical Properties of Imidazolium-, Pyroldinium-, and Phosphonium-Based Ionic Liquids

Abstract: Densities, viscosities, speeds of sound, surface tensions, and refractive indices for nine different imidazolium-, pyroldinium-, and phosphonium-based ionic liquids were measured at temperatures ranging from 298.15 K to 333.15 K and atmospheric pressure. Empirical models were used to correlate the thermophysical properties of the ionic liquids as a function of temperature. The isentropic compressibility, coefficients of thermal expansion, surface properties, and critical temperatures were calculated using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 62 publications
6
77
1
1
Order By: Relevance
“…[C4C1im][BF4] in 14 papers, 12,15,19,23,27,28,83,103,106,112,113,117-119 and [C4C1im][PF6] in 19 papers 12,13,15,18,19,21,22,27,33,75,[87][88][89][105][106][107][108][109][110] . However, for [C4C1im][BF4], the identical speeds of sound data as obtained by Govinda et al 83 are reported by Kavitha et al 103 Garcia-Miaja et al 112,113 cited data published by Zafarani-Moattar and Shekaari.…”
Section: Overview Of Existing Data For Ionic Liquidsmentioning
confidence: 99%
“…[C4C1im][BF4] in 14 papers, 12,15,19,23,27,28,83,103,106,112,113,117-119 and [C4C1im][PF6] in 19 papers 12,13,15,18,19,21,22,27,33,75,[87][88][89][105][106][107][108][109][110] . However, for [C4C1im][BF4], the identical speeds of sound data as obtained by Govinda et al 83 are reported by Kavitha et al 103 Garcia-Miaja et al 112,113 cited data published by Zafarani-Moattar and Shekaari.…”
Section: Overview Of Existing Data For Ionic Liquidsmentioning
confidence: 99%
“…Therefore, imidazolium‐based ILs are used in our work due to their higher selectivity and lower viscosity. Since the selectivity of imidazolium‐based ILs is inversely proportional to their viscosity which is proportional to the length of cation side chain, [BMIM][Ac] is suggested as the solvent to separate the mixture of acetonitrile and ethanol. In order to verify the outstanding separation performance of [BMIM][Ac], the vapor–liquid equilibrium (VLE) data of the acetonitrile + ethanol +[BMIM][Ac] were determined at 101.3 kPa in the following section.…”
Section: Ionic Liquid Screenmentioning
confidence: 99%
“…41 Therefore, imidazolium-based ILs are used in our work due to their higher selectivity and lower viscosity. Since the selectivity of imidazolium-based ILs is inversely proportional to their viscosity which is proportional to the length of cation side chain, [55][56][57][58][59] [BMIM][Ac] is suggested as the solvent to separate the mixture of acetonitrile and ethanol. In order to verify Owing to their hygroscopicity, both ILs were desiccated at 365 K for 24 h using vacuum drying oven (DZF-6020, Boxun, Shanghai, China) prior to experiment, and the Karl Fisher (KF) titration was employed to detect the water content of ILs.…”
Section: Computational Detailsmentioning
confidence: 99%
“…where M 1 and M 2 are the molar masses of pure water and pure IL, respectively, x 2 is the mole fraction of IL in the aqueous solution, ρ, ρ 0 and ρ 1 are the densities of solution, pure water and pure IL [10,19] and figures 5, 6, respectively. Alternatively, the excess molar volume data can also be expressed in terms of the molality of solution at any temperature as,…”
Section: Tablementioning
confidence: 99%